PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PEMBANGUNAN INFRASTRUKTUR PERDESAAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT KECAMATAN WANASALAM KABUPATEN LEBAK - Ahmad Sururi (Program Studi Administrasi Negara Universitas Serang Raya, 2015)
This study aims to describe and analyze the empowerment of communities through the Rural Infrastructure Development Program (PPIP) in Improving Public Welfare Wanasalam District of Lebak.From the results of this study concluded that the Community Empowerment through Rural Infrastructure Development (PPIP) in improving public welfare Wanasalam District of Lebak has implemented 10 (ten) of the 12 (twelve) principles proposed community empowerment in Mardikanto Dahatma and Bhatnagar (2013: 106), then through the Community Empowerment for Rural Infrastructure Development (PPIP) in improving public welfare Wanasalam District of Lebak not carry two (2) principles of community empowerment which principles of community development cooperation is based on the analysis of the participation and empowerment of the principle of democratic society based on the analysis in the application science, this is due 1.Less public's understanding of the meaning of community empowerment and the existence of the Rural Infrastructure Development Program (PPIP), 2 Lack of socialization given by the community facilitators and institutional devices village in providing information on the activities and the lack of public awareness both as individuals and members of society concerning the conditions and environment, 3 There is a culture of compliance citizens against warlords (formal and informal leaders) that affect people's attitudes in policy decision making.